PENDEKATAN FUNGSIONALISME STRUKTURAL TALCOTT PERSON UPAYA MELESTARIKAN TRADISI KENDURI SKO MASYARAKAT KERINCI - Pritania, Nayes; Sandora, Lisna (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
As time progresses, there are more challenges faced. One of these challenges is the increasingly modern globalization, which can easily lead to the loss of existence of a culture and make it vulnerable to extinction. This research has two main objectives. First, to understand the existence of the